Hydrogen Diffusion: In Situ Monitoring of Lateral Hydrogen Diffusion in Amorphous and Polycrystalline WO3 Thin Films (Adv. Mater. Interfaces 6/2018). Issue 6 (26th March 2018) - Burkhardt, Simon; Elm, Matthias T.; Lani‐Wayda, Bernhard; Klar, Peter J.
Abstract : A microstructured polymer film on top of tungsten trioxide (WO3 ) allows for locally confined insertion of protons (green) from a liquid electrolyte and electrons from a transparent conducting oxide. The formation of atomic hydrogen (red) is accompanied by electrochromic coloration. The diffusive transport of hydrogen is resolved spatially and temporally via in‐situ transmission spectroscopy to reveal concentration‐dependent diffusion in WO3 . This is reported by Matthias T. Elm and co‐workers in article number1701587 .